2015
DOI: 10.1016/j.taap.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-induced carcinogenesis in human bronchial epithelial cells

Abstract: Metals such as arsenic, cadmium, beryllium, and nickel are known human carcinogens; however, other transition metals, such as tungsten (W), remain relatively uninvestigated with regard to their potential carcinogenic activity. Tungsten production for industrial and military applications has almost doubled over the past decade and continues to increase. Here, for the first time, we demonstrate tungsten’s ability to induce carcinogenic related endpoints including cell transformation, increased migration, xenogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Based on the evidence provided in this study and our previous investigations, 14 tungsten exposure should be a significant concern for human health despite its low cellular toxicity. Moreover, these findings should generate concern among regulatory agencies and industry to more seriously consider tungsten as a carcinogen.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Based on the evidence provided in this study and our previous investigations, 14 tungsten exposure should be a significant concern for human health despite its low cellular toxicity. Moreover, these findings should generate concern among regulatory agencies and industry to more seriously consider tungsten as a carcinogen.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, occupational exposures to tungsten raise significant toxicity concerns. Previously, we reported on tungsten's ability to induce cancer‐related endpoints including cell transformation, increased migration, xenograft growth in nude mice, and the activation of multiple cancer‐related pathways, following in vitro exposure to BEAS‐2B cells . Histone modifications have been identified following exposure to a number of other carcinogenic metals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several ecotoxicological studies have discovered that under certain environmental conditions, tungsten compounds can be solubilized and enter the biogeochemical cycles [7,8]. Occupational studies on workers' exposure in industry where tungsten is used have revealed several adverse health effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten (W) is a metal toxin with suspected carcinogenic properties [1][2][3][4]. As a dense lithophilic element noted for its hardness, superior electrical conductivity, high melting point and corrosion-resistance, W has a wide range of uses in daily household items (such as lamp filaments), building and construction tools (i.e.…”
Section: Introductionmentioning
confidence: 99%